Post‐traumatic stress disorder symptoms, underlying affective vulnerabilities, and smoking for affect regulation. (January 2015) - Mathew, Amanda R.; Cook, Jessica W.; Japuntich, Sandra J.; Leventhal, Adam M.
<x xml:space="preserve">Abstract</x> Background and Objectives Post‐traumatic stress disorder (PTSD) is overrepresented among cigarette smokers. It has been hypothesized that those with PTSD smoke to alleviate negative affect and counteract deficient positive affect commonly associated with the disorder; however, limited research has examined associations between PTSD symptoms, smoking motives, and affective vulnerability factors. In the current study, we examined (1) whether PTSD symptoms were associated with positive reinforcement and negative reinforcement smoking motives; and (2) whether two affective vulnerability factors implicated in PTSD—anxiety sensitivity and anhedonia—mediated relationships between PTSD symptoms and smoking motives. Methods Data were drawn from a community sample of non‐treatment‐seeking smokers recruited without regard for trauma history (N = 342; 10+ cig/day). We used the Posttraumatic Stress Disorder Checklist‐Civilian Version (PCL‐C) to assess overall PTSD symptom severity as well as individual PTSD subfactors. Results Overall, PTSD symptom severity was significantly associated with negative reinforcement, but not positive reinforcement, smoking motives. Variation in anxiety sensitivity significantly mediated the relation between PTSD symptom severity and negative reinforcement smoking motives, whereas anhedonia did not. Regarding PTSD subfactors, emotional numbing was the only PTSD subfactor associated with smoking rate, while re‐experiencing symptoms were uniquely associated with both positive reinforcement and negative reinforcement smoking motives. Conclusions and Scientific Significance Findings suggest that anxiety sensitivity may be an important feature associated with PTSD that enhances motivation to smoke for negative reinforcement purposes. Smoking cessation interventions that alleviate anxiety sensitivity and enhance coping with negative affect may be useful for smokers with elevated PTSD symptoms. (Am J Addict 2015;24:39–46)